Among-Species Differences in Seasonal Timing and Weather Correlates of Autumn Raptor Migration at Khao Dinsor, Thailand, 2015-2016 - Patricia P.K. (2023)
Identifying the drivers of shifts in the abundance of wildlife species has been a central focus of conservation ecology recently. With growing concern about the impacts of global environmental change on biodiversity patterns, ecologists are challenged to better understand the relationships between species' abundance and various environmental factors. Using raptor count data collected following a standardized protocol at Khao Dinsor, southern Thailand, in 2015 and 2016, we characterized the seasonal timing and identified weather associations of the visible migration of representative species, namely the Black Baza (Aviceda leuphotes), Chinese Sparrowhawk (Accipiter soloensis), and Oriental Honey-Buzzard (Pernis ptilorhynchus). We explored the associations of their daily total counts with local weather variables. We found that the magnitude of their migration within the season was linked with the prevailing meteorological conditions. In general, daily counts of all three species were positively associated with predominant wind patterns. Air temperature was positively associated with the daily counts of species that migrated early in the season (Chinese Sparrowhawk and Oriental Honey-Buzzard). Barometric pressure was negatively associated with the daily counts of species whose migration window coincides with the shift in monsoon season (Black Baza and Oriental Honey-Buzzard). These results provide us with a better understanding of the drivers of migration patterns at a representative monitoring site on a globally important and heavily used flyway. They may be useful for making better inferences and predictions on the population trajectories of migrating raptors in future environmental change scenarios.